Dunajska predmestna deklica pri Ivanu Cankarju in Arthurju Schnitzlerju - Čeh Steger, Jožica (Jezik in slovstvo, 2004)
At the turn of the 19th century into the 20th century, Ivan Cankar and Arthur Schnitzler chose as their main theme the Vienna suburbs and a girl living in that milieu, most frequently coming from the proletarian or bourgeois background, Cankar's suburban girl is not familiar with the erotic frivolousness and melancholic charm of Schnitzler's "süsses Mädel"; she is stili half-child, although aged, stili absorbed in thoughts, burdened with care for survival, frequently a witness to, or a victim of sexual abuse. From an ugly body and ordinary life in the suburbs, which she is experiencing as a prison, she escapes into the yearning world of pure beauty, though this often leads to her death. Great differences can be found between the Slovene and Austrian authors in the portrayal of this suburban female figure; however, the frequently employed topic of death correlated to art, identity crisis, and aestheticism of life are the themes linking the two authors
Keywords: avstrijska književnost; Cankar, Ivan, 1876-1918; literarni liki; metaforika; primerjalne študije; Schnitzler, Arthur, 1862-1931; Slovene literature; slovenska književnost